Pessaries (mechanical devices) for pelvic organ prolapse in women - Bugge, Carol (Cochrane Database Syst Rev, 2013)
BACKGROUND: Pelvic organ prolapse is common, with some degree of prolapse seen in up to 50% of parous women in a clinic setting, although many are asymptomatic. The use of pessaries (a passive mechanical device designed to support the vagina) to treat prolapse is very common, and up to 77% of clinicians use pessaries for the first line management of prolapse. A number of symptoms may be associated with prolapse and treatments include surgery, pessaries and conservative therapies. A variety of pessaries are described which aim to alleviate the symptoms of prolapse and avert or delay the need for surgery. OBJECTIVES: To determine the effectiveness of pessaries (mechanical devices) for pelvic organ prolapse. SEARCH METHODS: We searched the Cochrane Incontinence Group Specialised Register of trials (searched 13 March 2012), which includes searches of CENTRAL, MEDLINE, PREMEDLINE and handsearching of conference proceedings, and handsearched the abstracts of two relevant conferences held in 2011. We also searched the reference lists of relevant articles. SELECTION CRITERIA: Randomised and quasi‐randomised controlled trials which included a pessary for pelvic organ prolapse in one arm of the study. DATA COLLECTION AND ANALYSIS: Abstracts were assessed independently by two authors with arbitration from a third if necessary. Data extraction was completed independently for included studies by two review authors. MAIN RESULTS: To date there is only one published randomised controlled trial assessing the use of pessaries in the treatment of pelvic organ prolapse. AUTHORS' CONCLUSIONS: The review authors identified one randomised controlled trial comparing ring and Gellhorn pessaries. The results of the trial showed that both pessaries were effective for the approximately 60% of women who completed the study with no significant differences identified between the two types of pessary. However, methodological flaws were noted in the trial, as elaborated under risk of bias assessment. There is no consensus on the use of different types of device, the indications nor the pattern of replacement and follow‐up care. There is an urgent need for randomised studies to address the use of pessaries in comparison with no treatment, surgery and conservative measures.